Le récit du cirque... De la vallée des morts de Mohamed Alioum-Fantouré (1975) : une écriture transgénérique et translittéraire - Angui, Aimé (Estudios Románicos, 2016)
Contrary to some writers of the first generation whose narrative frame- work new linear and “architext” uniform, Alioum Fantouré is breaking new ground through what the so called New African Novel. As a mater of fact, in Le Récit du Cirque..., he combines poetry with drama, the natural with the supernatural to bring forth“writing” with a dramatic and pathetic flavor.